2019
DOI: 10.1002/elps.201800402
|View full text |Cite
|
Sign up to set email alerts
|

The influence of MTHFR C677T polymorphism in chronic lymphocytic leukemia

Abstract: Some factors have been associated with the etiology of chronic lymphocytic leukemia (CLL), among them the Methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism. The aim of this study was to evaluate the role of MTHFR C677T polymorphism in CLL. A case‐control study was conducted with 219 individuals from Brazilian central population. MTHFR C677T polymorphism was determined through PCR‐RFLP followed by PAGE. The T allele frequence was higher in patients diagnosed with CLL than healthy subjects. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This result is associated especially with the elderly male (Rodrigues et al, 2016;Hallek et al, 2019). It is suggested that this type of neoplasia presents a higher prevalence in male, being more common with advancing age, especially in Western countries (Reis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is associated especially with the elderly male (Rodrigues et al, 2016;Hallek et al, 2019). It is suggested that this type of neoplasia presents a higher prevalence in male, being more common with advancing age, especially in Western countries (Reis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Catovsky et al (2014) suggested that differences between the gender for development and response to therapy in CLL may be associated with the effect of estrogen level. Moreover, a Brazilian study demonstrated that age is linked to CLL predisposition for Methylenetetrahydrofolate reductase (MTHFR) rs1801133 SNP (Reis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants of angiogenesis factors can influence the expression of the corresponding proteins, and thus modify susceptibility to and severity of cancer. Indeed, some authors suggest an association between polymorphisms and predisposition to B-CLL development [38,39]…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants of angiogenesis factors can influence the expression of the corresponding proteins, and thus modify susceptibility to and severity of cancer. Indeed, some authors suggest an association between polymorphisms and predisposition to B-CLL development [38,39] and formation of specific chromosomal aberrations [40]. Other researchers have described some polymorphisms variants linked with the prediction of clinical outcome [41].…”
Section: Discussionmentioning
confidence: 99%
“…The results were observed in PAGE stained with silver nitrate. The PCR‐RFLP technique is widely used for genotyping because it is a simple procedure, low cost and high reproducibility when compared to other molecular methods 11,12 …”
Section: Methodsmentioning
confidence: 99%